SURGICAL SITE INFECTION WITH EXTREME DRUG-RESISTANT ACINETOBACTER BAUMANII: A WAKE-UP CALL! - Faraz Waheed; Afaq Saeed Khan; Usman Babar; Manahil Saeed Khan (Journal of Ayub Medical College Abbottabad, 2024)
Surgical site infections are a common complication of surgery with a high prevalence in lower middle-income countries (LMICS). Excessive focus on antibiotic prophylaxis to prevent surgical site infections while neglecting other precautions like aseptic measures, patient nutrition, proper wound care has resulted in the emergence of antibiotic resistant microbials. Such organisms are a menace to healthcare. They cause prolonged hospital stay, use of expensive drugs, increased mortality and morbidity and overall, greatly increased cost of care per patient. We present a case of extreme drug resistant Acinetobacter spp causing surgical site infection following abdominal surgery, from Peshawar, Pakistan. Our patient was an 18-year-old lady who had undergone abdominoplasty following which she developed high grade fever, pain in abdomen and wound discharge. Empiric antibiotics treatment did not improve her condition. Culture and sensitivity report showed the growth of Acinetobacter spp. Which was resistant to almost all of the commonly used antibiotics, with the exception of tigecycline. Patient was treated with tigecycline which resolved her fever and wound infection and she was discharged in a stable condition. We believe our case highlights the importance of antibiotics stewardship and is a wakeup call to healthcare professionals and policy makers to take necessary steps to herald the danger of antibiotics resistance before it is too late.